Post COVID-19 Pandemic Scenarios in an Unequal World Challenges for Sustainable Development in Latin America - Morea, Juan Pablo (2020)
The COVID-19 pandemic has prompted numerous academic debates about its impact on health and the economy and on possible post-pandemic scenarios across the globe. The discussion has been focused on whether the pandemic will mark a turning point and a unique opportunity to generate radical changes in the economic and productive system, or if the State assistance role will, once again, serve to rescue the capitalist system. There is a common link between these two opposing positions in that there will be a crossroads for the future of humanity, regarding the treatment that will be given to nature. However, some of the most optimistic visions seem to underestimate the different realities that the world presents. This paper proposes a combined analysis about the possible post-pandemic scenarios that are debated at a global level, and the impacts of the pandemic in the context of Latin America to fill an information gap and to aid understanding on what the possible post-pandemic scenarios for Latin America could be. The first findings show that the debates about the post-pandemic future at the global level could be grouped between: the return to “business as usual”; a managed transition; and a paradigm shift. For Latin America, the post-pandemic scenario will be highly conditioned on how the new world order is reconfigured, and moving on a path towards sustainability for the region in the post-pandemic scenario seems to be linked to two possibilities: a kind of revolt or revolution fostered by the social bases; or a solution of a global nature that favors making long-term decisions. If this does not occur, the most likely scenario seems to be a return to business as usual.